Correlation of orthodontic treatment motivation and the level of treatment needs based on the index of orthodontic treatment need (IOTN) of orthodontic patients - Ernata, Rissa Zharfany; Gayatri, Gita; Suwargiani, Anne Agustina (Universitas Padjadjaran, 2020)
Introduction: Malocclusion has an impact on the quality of life, thus becoming the motivation for orthodontic treatment. Subjective and objective needs for orthodontic treatment vary, where subjective needs are sometimes higher or maybe lower than objective needs, vice versa. The Index of Orthodontic Treatment Need (IOTN) is an index used to see the level of treatment needs. This study was aimed to analyse the correlation of orthodontic treatment motivation and the level of treatment needs based on the index of orthodontic treatment need (IOTN) of orthodontic patients. Methods: The research was correlation analytical. The motivation for orthodontic treatment was assessed using a questionnaire consisted of aspects of oral health motivation, oral function, aesthetics, psychosocial, and influence from others. The level of orthodontic treatment needs was assessed using the IOTN dental health component. Results: It was found that the patients’ motivation related to aesthetics was high. The motivation to get orthodontic treatment due to oral health, oral function, and psychosocial conditions was moderate, while related to the influence of others was low. The level of need for grade 4 treatment shows the largest percentage (48.57%). Gamma correlation analysis between motivation variables related to the oral and psychosocial function with the level of treatment needs showed a significantly positive correlation with the p-values of 0.003 and 0.022, categorized as weak correlation. Conclusion: There is a weak correlation of orthodontic treatment motivation and the level of treatment needs based on the index of orthodontic treatment need (IOTN) of orthodontic patients.